2014
DOI: 10.1364/josaa.31.00a195
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological hypothesis of color appearance and hue perception

Abstract: DeValois and DeValois (1993) showed that to explain hue appearance, S-cone signals have to be combined with M vs. L opponent signals in two different ways to produce red-green and yellow-blue axes respectively. Recently, it has been shown that color appearance is normal for individuals with genetic mutations that block S-cone input to blue-on ganglion cells. This is inconsistent with the DeValois hypothesis in which S-opponent konio-geniculate signals are combined with L−M signals at a 3rd processing stage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 69 publications
(105 reference statements)
1
66
0
Order By: Relevance
“…Response time important contribution of S-cone signals for both red-green and yellow-blue axes) have been shown to be more consistent with perceptual experience (26). When we repeated analyses using the multistage model, we found that the two kinds of model equally accounted for the color preference of normal trichromats (SI Text).…”
Section: Groupmentioning
confidence: 72%
“…Response time important contribution of S-cone signals for both red-green and yellow-blue axes) have been shown to be more consistent with perceptual experience (26). When we repeated analyses using the multistage model, we found that the two kinds of model equally accounted for the color preference of normal trichromats (SI Text).…”
Section: Groupmentioning
confidence: 72%
“…To explain hue appearance, S-cone signals have to be combined with M versus L opponent signals in two different ways to produce red-green and blue-yellow axes that match human perceptions, but only a small subset of midget ganglion cells need to carry S-cone signals to account for hue perception. Recordings from large samples of cells in the lateral geniculate nucleus (Tailby et al 2008) have identified a group of cells that have input from M cones with the same sign as S cones, for instance, they are (SþM)-L cells that we propose are the retinal locus responsible for blue perception (Schmidt et al 2014). Moreover, one population of cells in the lateral geniculate nucleus had L-(SþM) inputs as required for the yellow side of blue-yellow hue opponency and as predicted by the hypothesis that S-OFF signals may be injected directly into midget bipolar cells by the proposed GABA feed-forward mechanism.…”
Section: Recent Evidence Points To a New Hypothesis For The Biologicamentioning
confidence: 87%
“…Trichromats experience six basic color percepts that exist as opponent pairs: blue and yellow, red, and green, and black and white. In contrast, dichromats experience only four basic color percepts, nominally blue and yellow, and black and white, but they do not experience the normal sensations of red or green (Schmidt et al 2014). For all dichromats there are two colors that are indistinguishable from gray, one of which appears greenish and the other reddish to normal trichromats.…”
Section: Gene Therapy With L Opsin In Dichromatic Squirrel Monkeysmentioning
confidence: 94%
See 2 more Smart Citations